2016
DOI: 10.1128/iai.00307-16
|View full text |Cite
|
Sign up to set email alerts
|

Saliva-Induced Clotting Captures Streptococci: Novel Roles for Coagulation and Fibrinolysis in Host Defense and Immune Evasion

Abstract: Streptococcal pharyngitis is among the most common bacterial infections, but the molecular mechanisms involved remain poorly understood. Here we investigate the interactions among three major players in streptococcal pharyngitis: streptococci, plasma, and saliva. We find that saliva activates the plasma coagulation system through both the extrinsic and the intrinsic pathways, entrapping the bacteria in fibrin clots. The bacteria escape the clots by activating host plasminogen. Our results identify a potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Subsequently, Streptococci of groups A, C and G may shift the balance in the clotting cascade towards fibrinolysis, which may increase the probability of bleeding in the oral mucosa. This phenomenon has been repeatedly described in chronic inflammatory disease of the oral cavity . As response to fibrous deposits at wounded and inflamed sites in the oral mucosa, higher PFLs were found in patients with chronic inflammation in the oral cavity when compared to healthy subjects .…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Subsequently, Streptococci of groups A, C and G may shift the balance in the clotting cascade towards fibrinolysis, which may increase the probability of bleeding in the oral mucosa. This phenomenon has been repeatedly described in chronic inflammatory disease of the oral cavity . As response to fibrous deposits at wounded and inflamed sites in the oral mucosa, higher PFLs were found in patients with chronic inflammation in the oral cavity when compared to healthy subjects .…”
Section: Discussionmentioning
confidence: 57%
“…Even the microbiome in the oral cavity impacts on the delicate balance between fibrinogenesis and fibrinolysis. Wollein Waldetoft et al described that saliva activates the plasma clotting system via the extrinsic and intrinsic pathways of coagulation. Bacterial colonies are entrapped in the clots, but are able to escape by inducing fibrinolysis via secretion of streptokinase and activation of host plasminogen.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication, Wollein Woldetoft et al . have put forth a novel role for streptokinase in allowing colonization of the nasopharynx [76]. They first observed that human saliva was capable of activating both the extrinsic and intrinsic clotting cascades in human plasma, an exudate secreted in response to bacterial infection.…”
Section: Newly Discovered Roles For Virulence Factorsmentioning
confidence: 99%
“…ska Δ GAS mixed with saliva and plasma were quickly and permanently trapped in fibrin clots, while cells capable of secreting streptokinase could escape. They propose that this clotting reaction may be a mechanism to trap GAS on the mucosal surface to promote bacterial clearance, with streptokinase primarily acting to allow GAS to escape this immune mechanism [76]. The efficacy of these proposed mechanisms remains to be evaluated in vivo .…”
Section: Newly Discovered Roles For Virulence Factorsmentioning
confidence: 99%
“…Besides reducing blood loss, this would also contribute to the non‐specific host defence by reducing the risk of pathogens entering the blood. Wollein Waldetoft et al . reported that saliva may induce clotting of plasma through both extrinsic and intrinsic pathways of coagulation.…”
Section: Introductionmentioning
confidence: 99%